Menstrual Eduhub: Mobile-Based Menstrual Learning Application Using 3D Animation Technology - BINTI OMAR, PUTERI NUR HAZWANI; Binti Murli, Norhanifah (Applied Information Technology And Computer Science, 2024)
Menstrual health education is an important instrument for shifting culture about periods, particularly among students who undergo a variety of changes as they grow. While government-standardized textbooks have been the traditional way of conveying information, the market has seen growth in the application of menstrual education. Although these applications are widely available, they often lack specificity and fail to align with the KSSM syllabus. To address this issue, Menstrual Eduhub is aims to deliver a comprehensive educational experience for Form 1 student incorporating with quiz module to reinforce the students’ understanding of menstrual cycle through Multimedia Mobile Content Development (MMCD) technique. Moreover, this application incorporates clear 3D animations for each cycle phase, enhancing the learning process. User acceptance and functionality testing, measured using the System Usability Scale (SUS), yielded satisfactory results with a positive feedback rate of 86.50%, demonstrate that the Menstrual Eduhub application is effective as a learning aid for Form 1 students.